Rock engineering challenges in post-mining. Issue 1 (August 2021) - Alber, M
Abstract: A legacy of environmental challenges with abandoned mines remains for many generations. The challenges include among others: (i) danger from sinkholes above shallow old mine workings and (ii) effects of rising water level in deep mines. Abandoned shallow mines show after > 20 years no damaging subsidence. Sinkholes, however, may still develop by structurally controlled failure. Main contributing factors are the geometry of an underground opening. Geological factors include the resource type (orebody or seam), height of rock overburden and cohesive soil, water flow and discontinuity spacing. The latter determines the bulking factor of the displaced roof and thus the maximum caving height. For steeply inclined openings it must be considered whether the caved rock moves down the dip and prevents self-stabilization. Rising water levels in deep abandoned mines may induce seismic events. Despite significant progress in monitoring and numerical methods there is still no appropriate geological or rock mechanical basis for explaining or predicting water pressure induced seismic events. Some research topics are suggested to approach this issue.